2019
DOI: 10.14295/bds.2019.v22i1.1638
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive aesthetic rehabilitation in composite resin: report of two clinical cases

Abstract: Patient demand looking for the perfect smile has been steadily growing in the last few years. Thus, these two case reports discuss some ultra-conservatives approach to achieve good esthetic results. In the first case the clinical protocol of a restorative approach is described, the cosmetic remodeling of the teeth and in the second case, the replacement of extensive unsatisfactory composite restorations. The treatment planning was based on diagnostic waxing and the making of mock-up in both cases. Teeth bleach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
3
0
3
Order By: Relevance
“…The introduction of hybrid and micro-hybrid composites has made composites suitable for application on posterior teeth 20 . According to a research 98 out of 103 restorations reported to be successful which is a 95.1% success rate with a survival time of 12 years 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of hybrid and micro-hybrid composites has made composites suitable for application on posterior teeth 20 . According to a research 98 out of 103 restorations reported to be successful which is a 95.1% success rate with a survival time of 12 years 21 .…”
Section: Discussionmentioning
confidence: 99%
“…O planejamento reverso por meio das restaurações enceradas e do mock-up fornece segurança na execução de um tratamento funcional e estético (SOARES et al, 2016;REIS et al, 2018). Há um consenso entre diversos estudos apresentados em respeito à obtenção de resultados previsíveis no fechamento de diastemas, uma vez que o mock-up permite a análise prévia da forma, tamanho, simetria, nível incisal ideal e arquitetura da gengiva antes de realizar o tratamento definitivo (SIMON e MAGNE, 2008;KOVACS et al, 2011;OQUENDO, BREA e DAVID, 2011;OKIDA et al, 2012;SCHWARZ et al, 2013;SIGNORE et al, 2013;SOARES et al, 2014;THOMAS e DAVID, 2014;AKAN e BAGIS, 2016;BERWANGER et al, 2016;GARCÍA et al, 2016;MORITA et al, 2016;SOARES et al, 2016;ALBERTON et al, 2017;BRIANEZZI et al, 2017;REIS et al, 2017;MALULY-PRONI et al, 2018;REIS et al, 2018;PEDREIRA et al, 2019).…”
Section: Discussionunclassified
“…A utilização do mock-up foi empregada para dois tipos de tratamento, ou seja, foram realizados ensaios visando restaurações com resina composta ou fabricação de facetas cerâmicas, sendo que ambas foram realizadas por meio de desgastes dentários mínimos (SIMON e MAGNE, 2008;KOVACS et al, 2011;OQUENDO, BREA e DAVID, 2011;OKIDA et al, 2012;SCHWARZ et al, 2013;SIGNORE et al, 2013;SOARES et al, 2014;THOMAS e DAVID, 2014;AKAN e BAGIS, 2016;BERWANGER et al, 2016;GARCÍA et al, 2016;MORITA et al, 2016;SOARES et al, 2016;ALBERTON et al, 2017;BRIANEZZI et al, 2017;REIS et al, 2017;MALULY-PRONI et al, 2018;REIS et al, 2018;PEDREIRA et al, 2019 (2015).…”
Section: Discussionunclassified
“…We chose to perform the cervical margin relocation for the insertion of a portion of composite resin to the floor of the proximal box can be considered a fast procedure, with less technical sensitivity, than the cementation of a ceramic restoration with subgingival finishing line with the constant risk of contamination by blood/ saliva [6]. The rubber dam isolation, although it can be a complex procedure in some situations, can reduce the inclusion of defects in subsequent steps [27]. A clinical trial has shown that operator influence can impact negatively in the failure rate (about 10% reduction) [28].…”
Section: Operative Aspectsmentioning
confidence: 99%